2020
DOI: 10.5152/tjg.2020.18974
|View full text |Cite
|
Sign up to set email alerts
|

High-dose dual therapy is effective as first-line treatment for Helicobacter pylori infection

Abstract: Stem cells for pancreatitis 425 Gastric injury and bacterial overgrowth 433 The effect of visceral fat on SMA configuration 451 Antiplatelet agents in ulcerative colitis 459 Differentiation of BMSCs into intestinal ce 466 GERDOFF ® efficacy in patients with GERD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…Internet tools such as WeChat, as well as conducting regular follow-up of patients. Third, high-dose dual therapy could reduce unnecessary antibiotic use and the related disadvantages such as antibiotic resistance and ADR, and was expected to be a promising alternative regimen (Gao et al, 2020;Ozturk et al, 2020;Park et al, 2017). H. pylori enters replicative phase at an almost neutral pH 6−7, while at acid pH 3−6 it turns into its coccoid form which is resistant to antibiotics (Ierardi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internet tools such as WeChat, as well as conducting regular follow-up of patients. Third, high-dose dual therapy could reduce unnecessary antibiotic use and the related disadvantages such as antibiotic resistance and ADR, and was expected to be a promising alternative regimen (Gao et al, 2020;Ozturk et al, 2020;Park et al, 2017). H. pylori enters replicative phase at an almost neutral pH 6−7, while at acid pH 3−6 it turns into its coccoid form which is resistant to antibiotics (Ierardi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines of the Italian Society of Gastroenterology and Digestive Endoscopy suggested that PPI‐amoxicillin three times daily could act as rescue therapy if levofloxacin triple therapy failed (Romano et al, 2022). Nevertheless, in view of the low variety and potentially satisfactory eradication rate with high‐dose dual therapy that has been reported, it is worth conducting more dose ranging studies and prospective comparative trials to confirm its efficacy and safety in different countries, especially in antibiotic‐resistant regions (Malfertheiner et al, 2022; Ozturk et al, 2020).…”
Section: Treatment Strategies For H Pylori Infectionmentioning
confidence: 99%
“… 69 Another HDDT with rabeprazole in Turkey also achieved a satisfactory eradication rate of 91.3% ( Table 2 ). 70 More large-scale clinical studies are needed to formally promote HDDT into first-line therapy, especially in different populations, and to determine the types of PPI that can be used, the drug dosages, and the optimal frequency of administration.…”
Section: Empirical Treatmentmentioning
confidence: 99%
“…with high rates of corpus gastritis) and typically has required high doses of PPIs as measured in omeprazole equivalents. Recent studies in Asia where CYP2C19 rapid metabolizers are uncommon, parietal masses are low, and corpus gastritis is common to have shown that high‐dose PPI–amoxicillin can produce cure rates around 90% 16–23 . The effectiveness of the regimen is sensitive to factors such as total dose of amoxicillin, the frequency of amoxicillin and antisecretory drug administration, the duration/24‐h intragastric pH is maintained ≥6, and the duration of therapy.…”
Section: Vonoprazan–amoxicillin Dual Therapymentioning
confidence: 99%
“…Recent studies in Asia where CYP2C19 rapid metabolizers are uncommon, parietal masses are low, and corpus gastritis is common to have shown that high-dose PPI-amoxicillin can produce cure rates around 90%. [16][17][18][19][20][21][22][23] The effectiveness of the regimen is sensitive to factors such as total dose of amoxicillin, the frequency of amoxicillin and antisecretory drug administration, the duration/24-h intragastric pH is maintained ≥6, and the duration of therapy. Trials with PPIs suggested that 3 g of amoxicillin per day, a high potency PPI b.i.d., and duration of 14 days have proved effective.…”
Section: Vonoprazan-amoxicillin Dual Therapymentioning
confidence: 99%